"But is it Journalism?" Reflections on Online Informational Roles and Content Creation Practices of a Sample of South African Lawyers. Issue 3 (3rd July 2019) - Robertson, Heather; Dugmore, Harry
ABSTRACT: In the era of social media, journalism is no longer the preserve of journalists. In specialised fields, such as law, the public in general and lawyers and legal academics specifically are able to "push in" and report and comment publicly on legal matters including trials, commissions, acts of law passed in parliament and other legal processes. These contributions, as this paper explores, are reshaping the contours and content of public discussions of legal matters and of legal journalism in South Africa. This paper suggests that recent theorising of journalism role theory can help understand not just the motivations of these legal interlopers in the journalism space but also how they are shaping a new informational ecosystem in which legal issues, including human rights, administrative and criminal law, and other topics, are brought into the public domain. The paper explores what some South African lawyers understand about the roles they are playing in digital public spaces and how they perceive their contributions and their relationship to the journalism profession and to journalists within that profession. The paper suggests that these lawyers' practices challenge our understanding about how digital media informational ecosystems work and explores how this is impacting journalism in South Africa.